2019
DOI: 10.1111/jce.14210
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T‐wave morphology assessment from surface ECG is linked with cardiac events risk in genotype‐positive KCNH2 mutation carriers with normal QTc values

Abstract: Introduction Long QT syndrome (LQTS) mutation carriers have elevated the risk of cardiac events even in the absence of QTc prolongation; however, mutation penetrance in patients with normal QTc may be reflected in abnormal T‐wave shape, particularly in KCNH2 mutation carriers. We aimed to assess whether the magnitude of a three‐dimensional T‐wave vector (TwVM) will identify KCNH2‐mutation carriers with normal QTc at risk for cardiac events. Methods Adult LQT2 patients with QTc < 460 ms in men and <470 ms in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…drugs (Chen et al, 2000;Mitcheson et al, 2000;Mehta et al, 2018) in connection with the pharmacotherapy of LQTS at genetic levels (Mehta et al, 2018;Yin et al, 2018;Cortez et al, 2019;Kerr et al, 2019). The voltage activated potassium channel (Kv11.1) is encoded by the humane-ether-a-go-go related gene (hERG), which predominantly contributes to the electrical activity of the myocardium (Vandenberg et al, 2012;Vasseur et al, 2019).…”
Section: Kcnh2mentioning
confidence: 99%
“…drugs (Chen et al, 2000;Mitcheson et al, 2000;Mehta et al, 2018) in connection with the pharmacotherapy of LQTS at genetic levels (Mehta et al, 2018;Yin et al, 2018;Cortez et al, 2019;Kerr et al, 2019). The voltage activated potassium channel (Kv11.1) is encoded by the humane-ether-a-go-go related gene (hERG), which predominantly contributes to the electrical activity of the myocardium (Vandenberg et al, 2012;Vasseur et al, 2019).…”
Section: Kcnh2mentioning
confidence: 99%
“…However, a cutoff level equivalent to the one in our study, for patients with narrow QRS, was identified: 0.24 mV [16]. A recent study showed that Twvm <0.30 mV conferred a threefold increased risk of cardiac events in females with long QT syndrome (genotype-positive KCNH2 with normal QTc values) [17]. More studies, however, have evaluated frontal T-wave amplitudes, as opposed to the possibly superior three-dimensional vector used in our study.…”
Section: Discussionmentioning
confidence: 72%
“…A reduced QRS vector mag nitude (QRSvm) predicts ventricular arrhythmia in se lected cohorts [13][14][15]. A reduced Twave vector magni tude (Twvm) is a marker for ventricular repolarization changes, and a lower Twvm value has been associated with an increased risk of cardiac events [16,17].…”
Section: Introductionmentioning
confidence: 99%